PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP KOMITMEN PEGAWAI MELALUI KEPUASAN KERJA - Hery Purwono; Woro Utari; Indra Prasetyo (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
The aim of this research is to describe Perceived Organizational Support, job satisfaction, and organizational commitment of the Bojonegoro District Education Office. Testing and analyzing the effect of Perceived Organizational Support on job satisfaction. The effect of organizational support on organizational commitment. The effect of job satisfaction on organizational commitment. The effect of Perceived Organizational Support on organizational commitment through job satisfaction. This type of research is explanatory research with a quantitative approach. The population of this study were all employees of the Education Office of Bojonegoro Regency. The number of samples in this study was the entire population of 84 people using saturated sampling technique. This study uses the Structural Equation Modeling (SEM) method and the analytical tool used in this method is Smart PLS software. The results showed that Perceived Organizational Support, employee job satisfaction and organizational commitment of the Bojonegoro Regency Education Office were in very high conditions. Perceived Organizational Support has a significant effect on job satisfaction. Perceived Organizational Support has a significant effect on organizational commitment. Job satisfaction has a significant effect on organizational commitment. Perceived Organizational Support has a significant effect on organizational commitment through job satisfaction